The shock wave configuration used in nonlinear transmission lines to improve the voltage modulation depth - Silva Neto, L. P.; Santos Junior, V. C.; Rossi, J. O.; Barroso, J. J.; Schamiloglu, E.; Rangel, E. G.L.; Lima, G.; Santos, L. F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Nonlinear transmission lines (NLTLs) using varactor diodes can produce high-frequency waves on the order of some tens of megahertz. They reach only low power signals, and a way to improve the voltage modulation depth (VMD) without employing semiconductor devices is by using shock wave configuration. The shock wave configuration consists of several lines in parallel connected to the same source and the load. The main electrical parameters analyzed in these lines are frequency, VMD, power, and the number of lumped-element sections. This work proposes the shock wave configuration for improving the VMD using multiple NLTLs. NLTLs in the shock wave configuration were implemented on printed circuit boards and simulated by using the LT-Spice software. Simulation and tests of a single line with 7 lumped-sections produced an RF signal at a frequency of about 30 MHz, VMD around 0.79 V. On the other hand, by using a shock wave configuration with four lines, the VMD increased to 3.73 V, which means a gain of 4.72. Other parameters remained unchanged under the shock wave configuration.
Keywords: NLTLs; radiofrequency; shock wave configuration; varactor diode